Inherited bleeding disorders. (April 2021) - Ling, Gavin; Luo, Pu-Lin
Abstract: Inherited bleeding disorders (IBDs) encompass a large number of different but rare conditions that can lead to increased risk of bleeding. The most common IBDs are von Willebrand disease, haemophilia A and haemophilia B. The diagnosis of IBDs requires a detailed history of the bleeding and specialized coagulation testing. The management of bleeding episodes in patients with IBDs can include the use of coagulation factor concentrate, desmopressin and antifibrinolytics such as tranexamic acid. This brief review focuses on the more common IBDs.